Screens for piwi suppressors in Drosophila identify dosage-dependent regulators of germline stem cell division. - Smulders-Srinivasan, T.K.; Lin, H. (Genetics, 2003)
The Drosophila piwi gene is the founding member of the only known family of genes whose function in stem cell maintenance is highly conserved in both animal and plant kingdoms. piwi mutants fail to maintain germline stem cells in both male and female gonads. The identification of piwi-interacting genes is essential for understanding how stem cell divisions are regulated by piwi-mediated mechanisms. To search for such genes, we screened the Drosophila third chromosome ( approximately 36% of the euchromatic genome) for suppressor mutations of piwi2 and identified six strong and three weak piwi suppressor genes/sequences. These genes/sequences interact negatively with piwi in a dosage-sensitive manner. Two of the strong suppressors represent known genes--serendipity-delta and similar, both encoding transcription factors. These findings reveal that the genetic regulation of germline stem cell division involves dosage-sensitive mechanisms and that such mechanisms exist at the transcriptional level. In addition, we identified three other types of piwi interactors. The first type consists of deficiencies that dominantly interact with piwi2 to cause male sterility, implying that dosage-sensitive regulation also exists in the male germline. The other two types are deficiencies that cause lethality and female-specific lethality in a piwi2 mutant background, revealing the zygotic function of piwi in somatic development.